Pleural dissemination of epithelioid hemangioendothelioma diagnosed using semi-rigid thoracoscopic pleural cryobiopsy - Tomoya Horiguchi; Shin Hasegawa; Yoshiko Shigeyasu; Nanami Kiryu; Maki Ota; Shotaro Okachi; Yasuhiro Goto; Naozumi Hashimoto; Kenji Kawada; Kazuyoshi Imaizumi (Respiratory Medicine Case Reports)
Epithelioid hemangioendothelioma (EHE) with pleural involvement presents significant diagnostic challenges, particularly in terms of differentiating it from malignant pleural effusion caused by other types of cancer, such as lung carcinoma. While most cases of EHE follow an indolent course, some can deteriorate rapidly, particularly those with serosal involvement such as pleural metastasis. In this report, we describe a case in which semi-rigid thoracoscopic cryobiopsy under local anesthesia yielded adequate specimens safely for diagnosis of pleural dissemination of EHE. The patient was a 46-year-old woman who had been diagnosed with multifocal EHE affecting the liver and both lungs a decade earlier. After radiofrequency ablation for the hepatic lesions and 2 years of chemotherapy, she was monitored without specific treatment for approximately 8 years with no significant tumor progression. She presented to our department following a rapid increase in left-sided pleural effusion over the previous month. Based on the clinical course and imaging findings, the diagnosis was initially difficult. However, thoracoscopic cryobiopsy provided definitive confirmation of pleural EHE.